Distribution and contamination status of phthalic acid esters in the sediments of a tropical monsoonal estuary, Cochin – India. (November 2018) - Ramzi, A.; Gireeshkumar, T.R.; Habeeb Rahman, K.; Manu, Mohan; Balachandran, K.K.; Chacko, Jacob; Chandramohanakumar, N.
Abstract: Phthalic acid esters (PAEs) are a group of endocrine-disrupting chemicals listed as priority pollutants by United States Environmental Protection Agency (USEPA, 2009). This study provides baseline information on seasonal distribution and contamination status of six phthalic acid esters (∑6 PAEs) in sediments of a tropical estuary (Cochin-India). In general, the sediments accumulated more PAEs during the post monsoon (mean 2325 ngg −1 ; between 1402 and 3121 ngg -1 ) and monsoon (mean 1372 ngg −1 ; between 331 and 4015 ngg −1 ) periods indicating land run off as the major transport pathway. Moderate run off and comparatively high residence time lead to effective sorption and settling of PAEs in the surface sediments during post monsoon season. Despite a high discharge of PAEs in to the water column, their deposition on to the sediments occurs at a lower rate during monsoon than that post monsoon season. PAEs were (mean 810 ngg −1 ; between 44 and 1722 ngg -1 ) lowest in pre monsoon season. The pre monsoon season is characterized by a minimal runoff consequent to the trapping of these organic pollutants in the river catchment area. The mid and high molecular PAEs (DEHP-Di ethylhexyl phthalate, BBP-Benzyl butyl phthalate and DnBP-Di-n-butyl phthalate) were the dominant congeners relative to the low molecular weight congeners (DMP-Dimethyl phthalate and DEP-Diethyl phthalate). DEHP and BBP levels exceeded permissible risk levels indicating a serious ecological hazard to the estuarine ecosystem. Highlights: This study provides baseline information on PAEs in Cochin estuary, India. PAEs was in the range 44–1723 ngg -1 in pre monsoon, 331–1747 ngg -1 in monsoon and 1402–3121 ngg -1 in post monsoon. The predominant PAEs were DEHP, BBP, and DnBP. DEHP and BBP in sediments exceeded permissible risk levels. The estuary is significantly contaminated with PAEs.